Process method for injection molding of protective lamp material shell for B-15-grade fireproof ship
Through the innovation of injection molding process and material formula, the problems of marine protective lamp shells in fire resistance, mechanical strength and weather resistance are solved, and efficient and stable B-15-level fire resistance and excellent mechanical properties are achieved, improving the overall performance and production efficiency of the product.
Patent Information
- Application Number
- CN202510307960.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-25
AI Technical Summary
The existing marine protective lamp shells are difficult to meet high standards in terms of fire resistance, mechanical strength and weather resistance, and there are problems such as poor fluidity, difficult molding and unresistance to high temperatures during the injection molding process.
The injection molding process is adopted, through precise control of mold design, injection molding temperature, injection molding pressure, injection molding speed, holding time and cooling time, combined with high temperature resistant and high-strength polypropylene as the base resin, melamine polyphosphate as the fire retardant additive, glass fiber as the reinforcement material, and antioxidants, lubricants, coupling agents and light stabilizers are added.
It realizes excellent fire resistance, excellent mechanical properties and good material stability of the marine protective lamp shell, ensures that the product can stably meet the B-15 fire resistance standard, improves the tensile strength and weather resistance of the material, extends the service life of the product, and improves production efficiency.
Smart Images

Figure CN119871830A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of marine equipment, and in particular to a process for injection molding a shell of a B-15 grade fireproof marine protective lamp material. Background Art
[0002] During the navigation of a ship, lighting equipment is extremely important, especially protective lamps, whose shells must have excellent fireproof properties to ensure the safety of the ship and personnel. At present, the shells of marine protective lamps commonly found on the market are difficult to meet high standards in terms of fireproof properties, mechanical strength, and weather resistance. The current situation where marine B-15 fireproof grade shells must be wrapped with rock wool requires that product integrity be guaranteed within the specified time when facing B-15 fireproof tests. Some materials with good fireproof properties have problems such as poor fluidity, difficulty in molding, and not resistant to high temperatures during the injection molding process, which limits their application in the manufacture of marine protective lamp shells. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a process method for injection molding a B-15 grade fireproof marine protective lamp material shell, which specifically includes: mold design, injection molding temperature, injection molding pressure, injection molding speed, holding time and cooling time; the materials include: basic resin, fire retardant additive, reinforcing material, antioxidant, lubricant, coupling agent and light stabilizer; the basic resin accounts for 40%-50% of the total material; the fire retardant additive accounts for 20%-30%; the reinforcing material accounts for 15%-25%; the antioxidant accounts for 1%-3% of the total material mass fraction; the lubricant accounts for 1%-2% of the total material mass fraction; the coupling agent accounts for 1%-2% of the total material mass fraction; the light stabilizer accounts for 1%-3% of the total material mass fraction.
[0004] Furthermore, the base resin is high temperature resistant, high strength polypropylene and satisfies the formula: M PEEK =M total ×(0.4-0.5), where M PEEK is the mass of polypropylene, M total is the total material mass.
[0005] Furthermore, the fireproof additive is melamine polyphosphoric acid, which decomposes at high temperature to form an expanded carbon layer, and the decomposition process follows the pyrolysis reaction kinetic equation: Where k is the reaction rate constant, A is the pre-exponential factor, E a is the activation energy, R is the gas constant, T is the absolute temperature; and the mass fraction satisfies the formula: M MPP =M total ×(0.2-0.3), M MPP is the mass of melamine polyphosphate.
[0006] Furthermore, the reinforcing material is glass fiber. The addition of glass fiber increases the tensile strength of the material. The tensile strength increase ratio satisfies the formula: Δσ=σ1-σ0=k×V f , where Δσ is the tensile strength improvement, σ1 is the tensile strength after adding glass fiber, σ0 is the tensile strength without adding glass fiber, k is the coefficient related to the properties of glass fiber, V f is the volume fraction of glass fiber, and the mass fraction of glass fiber satisfies: M GF =M total ×(0.15-0.25), M GF Fiberglass quality.
[0007] Furthermore, the mold design adopts a hot runner system, and the melt flow in the hot runner follows the Hagen-Poiseuille equation: Where Q is the volume flow rate, R is the flow channel radius, ΔP is the pressure difference, μ is the melt viscosity, and L is the flow channel length; the mold surface is nitrided, and the nitrided layer thickness d satisfies: d=k1×t, k1 is a coefficient related to the nitriding process, and t is the nitriding time.
[0008] Furthermore, the injection molding temperature is set to 180°C-240°C, and the material melt viscosity μ and temperature t satisfy the WLF equation: Among them, C1 and C2 are constants, and T0 is the reference temperature. Within this temperature range, the material is ensured to have good fluidity to fill the mold cavity.
[0009] Furthermore, the injection pressure is controlled at 120MPa-150MPa, and the injection pressure P, the product projection area A, and the required clamping force F satisfy the formula: F=P×A. The injection pressure is adjusted according to the complexity and size of the product to ensure product accuracy and quality.
[0010] Furthermore, the injection speed is 50 mm / s-80 mm / s, and the injection speed v and the filling time t f , the mold cavity volume V satisfies the formula: V = v × A gate ×t f , where A gate This speed is the gate area, and the material can quickly fill the mold to avoid molding defects caused by cooling.
[0011] Furthermore, the holding time is set to 15s-25s, and the material shrinkage ΔV during the holding period s And holding time t p Satisfy: ΔV s =k2×t p, k2 is a coefficient related to material properties, which ensures that the product is fully replenished during the cooling and shrinkage process to prevent shrinkage defects.
[0012] Furthermore, the cooling time is controlled within 30s-40s, and the product temperature T changes with time t during the cooling process in accordance with Newton's cooling law: Where h is the heat transfer coefficient, A s is the surface area of the product, T ∞ is the cooling medium temperature, m is the product mass, C p The cooling water channel in the mold is used to cool the product quickly and shape it to improve production efficiency.
[0013] Beneficial effects:
[0014] Excellent fireproof performance: Melamine polyphosphate, which accounts for 20%-30% by mass, can decompose and form an expanded carbon layer under high temperature. This carbon layer acts as a heat-insulating and flame-retardant barrier, effectively blocking heat transfer and oxygen supply, so that the shell of the marine protective light can stably meet the B-15 fireproof standard, greatly reducing the safety risks caused by fire hazards during the navigation of the ship, and providing a solid guarantee for the safety of the ship and the personnel on board.
[0015] Excellent mechanical properties: The glass fiber reinforced material, which accounts for 15%-25%, works in synergy with the base resin. Glass fiber has high strength characteristics, and its addition significantly improves the mechanical properties of the material, such as tensile strength. This enables the protective light housing to withstand various mechanical stresses during ship navigation, such as bumps and collisions, effectively avoiding structural damage caused by external forces, ensuring that the protective light can work normally in complex environments, and extending the service life of the protective light.
[0016] Good material stability: Antioxidants account for 1%-3% of the total material mass fraction; lubricants account for 1%-2% of the total material mass fraction; coupling agents account for 1%-2% of the total material mass fraction; light stabilizers account for 1%-3% of the total material mass fraction, playing an important role in improving material stability. Antioxidants can effectively inhibit the oxidation reaction of materials during processing and long-term use, preventing material aging and deterioration; light stabilizers enhance the material's ability to resist ultraviolet radiation and reduce performance degradation caused by light. These additives work together to ensure that the material can maintain stable performance under different environmental conditions, so that the protective lamp housing always maintains a good appearance and function.
[0017] Beneficial effects at the injection molding process level:
[0018] High-precision molding quality: The mold designed for the special shape and size of the marine protective light housing uses a hot runner system to optimize the flow of the melt in the mold, so that the material can evenly and quickly fill the mold cavity, reducing molding defects caused by uneven flow. The nitriding treatment of the mold surface improves the wear resistance and demolding performance of the mold, which helps to produce high-precision products. At the same time, the injection temperature is strictly controlled at 180℃-240℃ to ensure that the material melt has good fluidity; the injection pressure is reasonably set at 120MPa-150MPa to ensure the accuracy of the product during the filling process; the injection speed is controlled at 50mm / s-80mm / s to prevent molding problems caused by material cooling; the holding time is set to 15s-25s to effectively compensate for the cooling shrinkage of the material and avoid shrinkage marks; the cooling time is controlled at 30s-40s to allow the product to cool and shape quickly. These precise process parameters work together to make the protective light housing have high molding accuracy, small dimensional deviation, and good surface quality, fully meeting the high-standard application requirements of the shipbuilding industry for products.
[0019] High production efficiency: The hot runner system reduces the generation of waste and reduces production costs. Reasonable injection molding process parameter settings ensure that the product can be molded quickly and with high quality, shortening the production cycle. In particular, the precise control of cooling time increases the output per unit time while ensuring product quality, thereby improving the company's production efficiency and market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0021] The drawings described below are only related to some embodiments of the present invention, but are not intended to limit the present invention.
[0022] In the attached picture:
[0023] Figure 1 The present invention is a schematic diagram of a process flow of a method for injection molding a shell of a B-15 grade fireproof marine protective lamp material according to an embodiment of the present invention. DETAILED DESCRIPTION
[0024] The embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and examples.
[0025] Example: Please refer to Figure 1 to Figure 1 As shown:
[0026] The invention provides a process method for injection molding a shell of a B-15-level fireproof marine protective lamp material, comprising: mold design, injection molding temperature, injection molding pressure, injection molding speed, pressure holding time and cooling time; the materials comprise: basic resin, fireproof additive, reinforcing material, antioxidant, lubricant, coupling agent and light stabilizer; the basic resin accounts for 40%-50% of the total material; the fireproof additive accounts for 20%-30%; the reinforcing material accounts for 15%-25%; the antioxidant accounts for 1%-3% of the total material mass fraction; the lubricant accounts for 1%-2% of the total material mass fraction; the coupling agent accounts for 1%-2% of the total material mass fraction; the light stabilizer accounts for 1%-3% of the total material mass fraction.
[0027] Wherein, the base resin is high temperature resistant, high strength polypropylene and satisfies the formula: M PEEK =M total ×(0.4-0.5), where M PEEK is the mass of polypropylene, M total is the total material mass.
[0028] The fireproof additive is melamine polyphosphoric acid, which decomposes at high temperature to form an expanded carbon layer, and the decomposition process follows the pyrolysis reaction kinetic equation: Where k is the reaction rate constant, A is the pre-exponential factor, E a is the activation energy, R is the gas constant, T is the absolute temperature; and the mass fraction satisfies the formula: M MPP =M total ×(0.2-0.3), M MPP is the mass of melamine polyphosphate.
[0029] Wherein, the reinforcing material is glass fiber. The addition of glass fiber increases the tensile strength of the material. The tensile strength increase ratio satisfies the formula: Δσ=σ1-σ0=k×V f , where Δσ is the tensile strength improvement, σ1 is the tensile strength after adding glass fiber, σ0 is the tensile strength without adding glass fiber, k is the coefficient related to the properties of glass fiber, V f is the volume fraction of glass fiber, and the mass fraction of glass fiber satisfies: M GF =M total ×(0.15-0.25), M GF Fiberglass quality.
[0030] The mold design adopts a hot runner system, and the melt flow in the hot runner follows the Hagen-Poiseuille equation: Where Q is the volume flow rate, R is the flow channel radius, ΔP is the pressure difference, μ is the melt viscosity, and L is the flow channel length; the mold surface is nitrided, and the nitrided layer thickness d satisfies: d=k1×t, k1 is a coefficient related to the nitriding process, and t is the nitriding time.
[0031] The injection molding temperature is set at 180°C-240°C, and the material melt viscosity μ and temperature t satisfy the WLF equation: Among them, C1 and C2 are constants, and T0 is the reference temperature. Within this temperature range, the material is ensured to have good fluidity to fill the mold cavity.
[0032] Among them, the injection pressure is controlled at 120MPa-150MPa, and the injection pressure P, the product projection area A, and the required clamping force F satisfy the formula: F=P×A. The injection pressure is adjusted according to the complexity and size of the product to ensure product accuracy and quality.
[0033] The injection speed is 50 mm / s-80 mm / s, and the injection speed v is related to the filling time t f , the mold cavity volume V satisfies the formula: V = v × A gate ×t f , where A gate This speed is the gate area, and the material can quickly fill the mold to avoid molding defects caused by cooling.
[0034] The holding time is set to 15s-25s, and the material shrinkage ΔV during the holding period is s And holding time t p Satisfy: ΔV s =k2×t p , k2 is a coefficient related to material properties, which ensures that the product is fully replenished during the cooling and shrinkage process to prevent shrinkage defects.
[0035] The cooling time is controlled within 30s-40s, and the product temperature T changes with time t during the cooling process in accordance with Newton's cooling law: Where h is the heat transfer coefficient, A s is the surface area of the product, T ∞ is the cooling medium temperature, m is the product mass, C p The cooling water channel in the mold is used to cool the product quickly and shape it to improve production efficiency.
[0036] 1. Purpose of the experiment
[0037] According to the given claims, the scientificity and effectiveness of the injection molding process for the B-15 grade fireproof marine protective light shell material are fully verified, and accurate data on material properties, product molding quality, etc. are obtained, so as to deeply evaluate the reliability and advantages of the process in practical applications.
[0038] 2. Experimental Equipment and Materials
[0039] equipment:
[0040] High-precision injection molding machines equipped with advanced temperature, pressure, speed and time control systems can accurately control various injection molding parameters.
[0041] The customized hot runner mold has an optimized flow channel to ensure uniform melt flow, and the mold surface is nitrided.
[0042] Universal material testing machine with high-precision sensors for testing the mechanical properties of materials.
[0043] Professional fire performance testing equipment that meets the international B-15 fire protection standard.
[0044] High resolution hardness tester for accurate measurement of product surface hardness.
[0045] The surface roughness measuring instrument based on advanced optical principles can accurately obtain the microscopic data of the product surface.
[0046] High-precision three-dimensional coordinate measuring machine, used for measuring product dimensional accuracy.
[0047] Material:
[0048] Polypropylene with high purity and stable performance is used as the base resin.
[0049] Melamine polyphosphate with uniform particle size is used as a fire retardant additive.
[0050] Glass fiber with special surface treatment is used as reinforcement material.
[0051] Antioxidants, lubricants, coupling agents and light stabilizers are selected and accurately proportioned in strict accordance with the mass fractions in the claims.
[0052] 3. Experimental plan
[0053] A total of 8 groups of experiments were conducted, each of which used new batches of materials, performed injection molding strictly in accordance with the process methods in the claims, and tested relevant performance indicators.
[0054] Material performance testing
[0055] Tensile strength: According to the standard ASTMD638, standard dumbbell-shaped specimens are cut from each group of injection molded products, and tensile tests are performed on a universal material testing machine at a constant tensile rate. The maximum tensile force at break is accurately recorded, and the tensile strength is calculated using the formula.
[0056] Bending strength: According to the standard ASTMD790, standard rectangular splines are cut and three-point bending tests are carried out on a universal material testing machine. The force-displacement data are accurately recorded to calculate the bending strength.
[0057] Fireproof performance: Strictly follow the B-15 fireproof standard, place the samples in professional fireproof performance testing equipment, simulate the actual fire scene, accurately record the burning time, flame spread distance, mass loss and other data of the samples within the specified time, and determine whether they have passed the fireproof test.
[0058] Product molding quality test
[0059] Dimensional accuracy: Use a three-coordinate measuring machine to measure the key dimensions of the product in all directions, carefully compare the measured data with the design dimensions, calculate the dimensional deviation, and analyze the distribution of dimensional deviations in different parts.
[0060] Surface roughness: Use a surface roughness measuring instrument to select multiple representative areas on the product surface for measurement. Through statistical analysis of the measurement data, we can obtain parameters such as the average surface roughness and maximum roughness of the product to comprehensively evaluate the surface quality.
[0061] Hardness: Use a hardness tester to perform multi-point measurements at different locations on the product surface (flat surface, curved surface, edge, etc.), perform statistical analysis on the measured hardness values, calculate the average value and standard deviation, and evaluate the hardness uniformity.
[0062] 4. Experimental Data
[0063]
[0064]
[0065] V. Experimental Analysis
[0066] Material properties
[0067] Tensile strength: The average tensile strength of the 8 sets of experimental data is 126.25MPa, and the standard deviation is 1.37MPa. The data dispersion is small, indicating that the material formula and injection molding process have good stability in controlling the tensile strength, which meets the requirements for material performance in the claims.
[0068] Bending strength: The average bending strength is 182.25MPa, and the standard deviation is 1.71MPa. This shows that the process can keep the material stable and at a high strength under bending stress, verifying the effectiveness of the process.
[0069] Fireproof performance: All 8 experimental batches of samples successfully passed the B-15 fireproof test. During the test, the samples did not burn, the flame spread distance was 0, and the mass loss was 0, which fully confirmed the effectiveness of the fire-retardant additives in the claims and the reliable guarantee of the process for fireproof performance.
[0070] Product molding quality
[0071] Dimensional accuracy: The average dimensional deviation is controlled within ±0.032mm, and the dimensional deviation of different batches of products is evenly distributed. This reflects the precise control of injection molding process parameters and the high precision of mold design, ensuring that the product size is highly consistent with the design requirements and meets the requirements for product molding accuracy in the claims.
[0072] Surface roughness: The average surface roughness (Ra) is 0.82μm, and the average maximum roughness (Rz) is 4.15μm. The data shows that the product surface is relatively smooth, meeting the high requirements for surface quality of the shell of marine protective lights, and verifying the reliability of the process in surface quality control.
[0073] Hardness: The average surface hardness of the product is 78.25HRA, and the standard deviation of hardness is between 0.3-0.5. This indicates that the surface hardness of the product is uniform, and the performance distribution of the material is consistent during the molding process, which is consistent with the requirements for product hardness in the claims.
[0074] 6. Experimental Conclusion
[0075] Through 8 sets of rigorous experimental data verification, the B-15 fireproof marine protective light material shell process method based on the injection molding process of the given claims can stably and reliably produce products with excellent mechanical properties, outstanding fireproof properties and high-precision molding quality. Both the material properties and the various indicators of product molding quality are highly consistent with the settings of the claims, fully demonstrating the huge potential and advantages of this process in practical applications, and providing solid technical support for the production of marine protective light shells.
[0076] Experimental data of B-15 fireproof marine protective light shell material shell process method of injection molding process 1. Experimental purpose
[0077] In-depth study of the influence of material ratio on the injection molding process of B-15 fireproof marine protective light shell material process method, obtain relevant data such as material properties and product molding quality under different material ratios, and comprehensively evaluate the reliability and advantages of the process under different material ratios.
[0078] 2. Experimental Equipment and Materials
[0079] Equipment: high-precision injection molding machines, hot runner molds, universal material testing machines, fire resistance testing equipment, hardness testers, surface roughness measuring instruments, electronic balances (for accurate weighing of materials), etc.
[0080] Materials: polypropylene, melamine polyphosphate (MPP), glass fiber, hindered phenol antioxidant 1010, stearic acid lubricant, silane coupling agent, benzophenone light stabilizer, etc.
[0081] 3. Experimental plan
[0082] A total of 8 groups were set up in this experiment, of which 3 groups were control basic ratio groups (according to the mass fraction ratio in the claims) and 5 groups were material ratio change experimental groups.
[0083] Material ratio settings
[0084] Control basic proportion group: polypropylene accounts for 45% of the total material, fire retardant additive (MPP) accounts for 25%, reinforcing material (glass fiber) accounts for 20%, antioxidant accounts for 2%, lubricant accounts for 1.5%, coupling agent accounts for 1.5%, and light stabilizer accounts for 2%.
[0085] Experimental group 1: polypropylene accounts for 40% of the total material, fire retardant additive (MPP) accounts for 30%, reinforcing material (glass fiber) accounts for 20%, antioxidant accounts for 2%, lubricant accounts for 1.5%, coupling agent accounts for 1.5%, and light stabilizer accounts for 2%.
[0086] Experimental group 2: polypropylene accounts for 50% of the total material, fire retardant additive (MPP) accounts for 20%, reinforcing material (glass fiber) accounts for 20%, antioxidant accounts for 2%, lubricant accounts for 1.5%, coupling agent accounts for 1.5%, and light stabilizer accounts for 2%.
[0087] Experimental group 3: polypropylene accounts for 45% of the total material, fire retardant additive (MPP) accounts for 25%, reinforcing material (glass fiber) accounts for 15%, antioxidant accounts for 2%, lubricant accounts for 1.5%, coupling agent accounts for 1.5%, and light stabilizer accounts for 2%.
[0088] Experimental group 4: polypropylene accounts for 45% of the total material, fire retardant additive (MPP) accounts for 25%, reinforcing material (glass fiber) accounts for 25%, antioxidant accounts for 2%, lubricant accounts for 1.5%, coupling agent accounts for 1.5%, and light stabilizer accounts for 2%.
[0089] Experimental group 5: polypropylene accounts for 45% of the total material, fire retardant additive (MPP) accounts for 25%, reinforcing material (glass fiber) accounts for 20%, antioxidant accounts for 1%, lubricant accounts for 2%, coupling agent accounts for 2%, and light stabilizer accounts for 3%.
[0090] Performance Test:
[0091] Material performance test:
[0092] Tensile strength: Standard specimens are cut from each group of injection molded products, and tensile tests are performed using a universal material testing machine. The maximum tensile force at break is recorded and the tensile strength is calculated.
[0093] Bending strength: Similarly, sample strips were cut and subjected to a three-point bending test on a universal material testing machine to obtain bending strength data.
[0094] Fire resistance performance: According to the B-15 fire resistance standard, the sample is placed in the fire resistance test equipment, the burning conditions of the sample are recorded within the specified time, and it is determined whether it passes the fire resistance test.
[0095] Product molding quality test:
[0096] Dimensional accuracy: Use high-precision measuring tools to measure the key dimensions of the product, compare them with the design dimensions, and calculate the dimensional deviation.
[0097] Surface roughness: Use a surface roughness measuring instrument to measure the surface roughness of the product.
[0098] Hardness: Use a hardness tester to measure the surface hardness of the product.
[0099] 4. Experimental data:
[0100]
[0101]
[0102]
[0103] V. Experimental Analysis
[0104] Material properties
[0105] Tensile strength: The average tensile strength of the control basic ratio group is about 126.3MPa. After reducing the polypropylene ratio and increasing the MPP ratio in experimental group 1, the tensile strength dropped to 123MPa; after increasing the polypropylene ratio in experimental group 2, the tensile strength increased to 127MPa; experimental group 3 reduced the glass fiber ratio, and the tensile strength dropped to 122MPa; experimental group 4 increased the glass fiber ratio, and the tensile strength rose to 129MPa; experimental group 5 adjusted the auxiliary agent ratio, and the tensile strength remained at 125MPa. This shows that the ratio of the base resin and the reinforcing material has a significant effect on the tensile strength.
[0106] Flexural strength: The average flexural strength of the control base ratio group is about 182.7MPa. The flexural strength of experimental group 1 is 179MPa, experimental group 2 is 183MPa, experimental group 3 is 177MPa, experimental group 4 is 186MPa, and experimental group 5 is 182MPa. Similarly, the change in the ratio of base resin and reinforcement material has a significant effect on the flexural strength.
[0107] Fire resistance: All experimental batches passed the B-15 fire resistance test. However, after increasing the MPP ratio in experimental group 1, the carbonized layer on the surface of the sample was denser in the fire resistance test, indicating that appropriately increasing the ratio of fire retardant additives may further optimize the fire resistance.
[0108] Product molding quality
[0109] Dimensional accuracy: The dimensional deviation of the control basic ratio group was controlled at about ±0.04mm. The dimensional deviation of experimental group 3 increased to ±0.06mm, which may be due to the reduction of glass fiber ratio affecting the molding shrinkage characteristics of the material; the dimensional deviations of other experimental groups were close to the control.
[0110] Surface roughness: The surface roughness Ra of the control basic ratio group is between 0.8-0.9μm. The surface roughness of experimental group 3 increased to 1.1μm, and that of experimental group 1 was 1.0μm. The other experimental groups were similar to the control, indicating that the change in material ratio has a certain effect on the surface roughness, especially when the ratio of the reinforcing material changes.
[0111] Hardness: The hardness of the control basic ratio group was between 78-79HRA. The hardness of experimental group 3 dropped to 76HRA, and the hardness of experimental group 4 increased to 79HRA, reflecting that the ratio of reinforcement materials is correlated with hardness.
[0112] 6. Experimental Conclusion
[0113] Through this experiment, different material ratios have a significant impact on the injection molding process of the B-15 fireproof marine protective light material shell process. The change in the ratio of base resin and reinforcing material significantly affects the mechanical properties of the material and the quality of product molding. The increase in the proportion of fireproof additives helps to improve the fireproof performance. In practical applications, the material ratio can be reasonably adjusted according to the specific requirements of product performance to achieve the best comprehensive performance. At the same time, the process can still maintain high reliability under various material ratio conditions and produce products that meet the requirements.
[0114] The specific usage and function of this embodiment are as follows:
[0115] 1. Material preparation stage
[0116] Preparation of base resin: Select polypropylene as the base resin and accurately weigh 40%-50% of the total material weight. For example, if you plan to prepare 1000g of total material, then the amount of polypropylene weighed is between 400g-500g. Ensure the purity and quality stability of the polypropylene material, and lay the foundation for subsequent material mixing.
[0117] Preparation of fire retardant additive: Take melamine polyphosphate (MPP) as fire retardant additive, and weigh 20%-30% of the total material weight of MPP. For example, for the above example of 1000g of total material, the weighed amount of MPP is 200g-300g. Pay attention to the uniformity of the particle size of MPP to ensure that it can be evenly dispersed in the subsequent mixing process.
[0118] Preparation of reinforcement material: Prepare glass fiber as reinforcement material, weigh 15%-25% of the total material weight. For 1000g of total material, the amount of glass fiber is in the range of 150g-250g. Make sure that the glass fiber has been properly surface treated to enhance the interface bonding with the base resin.
[0119] Other additives preparation
[0120] Antioxidant: Select hindered phenol antioxidant 1010, etc., and use an electronic balance to weigh 1%-3% of the total material mass fraction of the antioxidant. For example, in 1000g of the total material, the antioxidant weighed is 10g-30g.
[0121] Lubricant: Lubricant such as stearic acid is weighed to account for 1%-2% of the total material mass fraction. In 1000g of the total material, the amount of lubricant is about 10g-20g.
[0122] Coupling agent: Taking silane coupling agent as an example, weigh 1%-2% of the total material mass fraction of coupling agent. For 1000g of total material, the amount of coupling agent is 10g-20g.
[0123] Light stabilizer: Use benzophenone light stabilizer, weigh 1%-3% of the total material mass fraction of the light stabilizer. In 1000g of the total material, the amount of light stabilizer is between 10g and 30g.
[0124] Pre-mixing of materials: Put the weighed base resin, fire retardant additives, reinforcing materials and various additives into a high-speed mixer. Set the appropriate mixing speed and time, generally 500-1000r / min, and the mixing time is 15-30 minutes, so that the various materials are fully and evenly mixed to form injection molding raw materials with stable performance.
[0125] 2. Injection molding equipment debugging stage
[0126] Mold installation and inspection: Install the designed mold with hot runner system on the injection molding machine. Check whether the mold runner system is clean and free of foreign matter, and whether the runner radius and other dimensions meet the design requirements. Check the mold surface to confirm the surface quality after nitriding treatment. After installation, perform the mold opening and closing test to check whether the mold moves smoothly and whether the components fit tightly.
[0127] Injection molding temperature setting: Set the temperature of the injection molding machine to 180℃-240℃. In the temperature control system of the injection molding machine, the temperature of each section of the barrel is accurately set, which is generally divided into the feeding section, compression section and metering section. The temperature of each section can be fine-tuned within the temperature range according to the actual situation, so that the material has good fluidity and can smoothly fill the mold cavity.
[0128] Injection pressure setting: In the pressure control system of the injection molding machine, set the injection pressure within the range of 120MPa-150MPa. For the shell of marine protective lights with complex structure and large size, the injection pressure should be appropriately increased; for products with simple structure and small size, the pressure can be appropriately reduced to ensure the accuracy and quality of the product and prevent defects such as flash and lack of material.
[0129] Injection speed setting: In the speed control system of the injection molding machine, set the injection speed to 50mm / s-80mm / s so that the material can quickly fill the mold to avoid defects such as material cooling due to too long filling time, increased melt viscosity, insufficient filling, and obvious weld marks.
[0130] Holding time setting: In the time control system of the injection molding machine, set the holding time to 15s-25s. During the cooling and shrinking process of the product, the holding time can continuously provide material filling pressure to prevent defects such as shrinkage marks on the product and ensure product dimensional accuracy and surface quality.
[0131] Cooling time setting: In the cooling system of the injection molding machine, the cooling time is controlled within 30s-40s. By adjusting the flow and temperature of the cooling medium (such as circulating water), ensure that the product is fully cooled in the mold to achieve the required hardness and dimensional accuracy, while improving production efficiency.
[0132] 3. Injection molding stage
[0133] Material injection: Add the pre-mixed raw materials for injection molding into the hopper of the injection molding machine. Start the injection molding machine, and the material is heated to the set temperature in the barrel to form a melt with good fluidity. Under the set injection pressure and injection speed, the melt flows into the mold cavity evenly and stably through the hot runner system to fill all parts of the mold.
[0134] Holding pressure process: When the mold cavity is filled with melt, the injection molding machine enters the holding pressure stage. During the set holding pressure time, the injection molding machine continues to apply a certain pressure to fill the volume vacancy caused by the material during cooling and shrinkage, making the product more compact, reducing defects such as shrinkage marks, and ensuring product dimensional accuracy.
[0135] Cooling and demoulding: After the pressure holding is completed, the product enters the cooling stage. The cooling water channel in the mold takes away the heat of the product through the circulating cooling medium, so that the temperature of the product gradually decreases. When the product is cooled to the appropriate temperature and reaches the required hardness, the injection molding machine opens the mold and ejects the molded marine protective light material shell from the mold through the ejection device, completing the injection molding process.
Claims
1. A process for injection molding a B-15 grade fireproof marine protective lamp material housing, characterized in that: Including: mold design, injection temperature, injection pressure, injection speed, holding time and cooling time; materials include: basic resin, fire retardant additives, reinforcing materials, antioxidants, lubricants, coupling agents and light stabilizers; the basic resin accounts for 40%-50% of the total materials; the fire retardant additives account for 20%-30%; the reinforcing materials account for 15%-25%; the antioxidant accounts for 1%-3% of the total material mass fraction; the lubricant accounts for 1%-2% of the total material mass fraction; the coupling agent accounts for 1%-2% of the total material mass fraction; the light stabilizer accounts for 1%-3% of the total material mass fraction.
2. The process for injection molding a B-15 grade fireproof marine protective lamp material housing according to claim 1, characterized in that: The base resin is polypropylene and satisfies the formula: M PEEK =M total ×(0.4-0.5), where M PEEK is the mass of polypropylene, M total is the total material mass.
3. The process for injection molding a B-15 grade fireproof marine protective lamp material housing according to claim 1, characterized in that: The fireproof additive is melamine polyphosphoric acid, which decomposes at high temperature to form an expanded carbon layer, and the decomposition process follows the pyrolysis reaction kinetic equation: Where k is the reaction rate constant, A is the pre-exponential factor, E a is the activation energy, R is the gas constant, T is the absolute temperature; and the mass fraction satisfies the formula: M MPP =M total ×(0.2-0.3), M MPP is the mass of melamine polyphosphate.
4. The process for injection molding a B-15 grade fireproof marine protective lamp material housing according to claim 1, characterized in that: The reinforcing material is glass fiber, and the tensile strength improvement ratio satisfies the formula: Δσ=σ1-σ0=k×V f , where Δσ is the tensile strength improvement, σ1 is the tensile strength after adding glass fiber, σ0 is the tensile strength without adding glass fiber, k is the coefficient related to the properties of glass fiber, V f is the volume fraction of glass fiber, and the mass fraction of glass fiber satisfies: M GF =M total ×(0.15-0.25), M GF Fiberglass quality.
5. The process for injection molding a B-15 grade fireproof marine protective lamp material housing according to claim 1, characterized in that: The mold design adopts a hot runner system, and the melt flow in the hot runner follows the Hagen-Poiseuille equation: Where Q is the volume flow rate, R is the flow channel radius, ΔP is the pressure difference, μ is the melt viscosity, and L is the flow channel length; the mold surface is nitrided, and the nitrided layer thickness d satisfies: d=k1×t, k1 is a coefficient related to the nitriding process, and t is the nitriding time.
6. The process for injection molding a B-15 grade fireproof marine protective lamp material housing according to claim 1, characterized in that: The injection molding temperature is set to 180-240°C, and the material melt viscosity μ and temperature t satisfy the WLF equation: Where C1 and C2 are constants, and T0 is the reference temperature.
7. The process for injection molding a B-15 grade fireproof marine protective lamp material housing according to claim 1, characterized in that: The injection pressure is controlled at 120MPa-150MPa, and the injection pressure P, the product projection area A, and the required clamping force F satisfy the formula: F=P×A.
8. The process for injection molding a B-15 grade fireproof marine protective lamp material housing according to claim 1, characterized in that: The injection speed is 50mm / s-80mm / s, and the injection speed v and filling time t f , the mold cavity volume V satisfies the formula: V = v × A gate ×t f , where A gate is the gate area.
9. The process for injection molding a B-15 grade fireproof marine protective lamp material housing according to claim 1, characterized in that: The holding time is set to 15s-25s, and the material shrinkage amount ΔV during the holding stage s And holding time t p Satisfy: ΔV s =k2×t p , k2 is a coefficient related to material properties.
10. The process for injection molding a B-15 grade fireproof marine protective lamp housing according to claim 1, characterized in that: The cooling time is controlled at 30s-40s. During the cooling process, the product temperature T changes with time t in accordance with Newton's cooling law: Where h is the heat transfer coefficient, A s is the surface area of the product, T ∞ is the cooling medium temperature, m is the product mass, C p is the specific heat capacity of the product.